2022
DOI: 10.3390/children9101477
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Toe Walking in Children with Autism Spectrum Disorder: “Cast and Go”

Abstract: Background: Toe walking is associated with autism spectrum disorders (ASD). Correction of this “behavior” is a health challenge. The toe walker is affected by the contact refusal with the outside world: touching the ground as little as possible, trying to avoid any contact. A structured equines foot is a possible consequence. Method: We present the “Cast and Go” protocol, used in 22 idiopathic toe walker children with ASD treated from 2015 to 2020. The treatment was performed by a single senior experienced doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Lim, O'Sullivan, Choi and Kim, 2016 [55] n = 30; ASD =15, male = 13 8.4-14 yrs. DSM-IV No Manfredi, Riefoli, Coviello and Dibello, 2022 [56] n = 22; ASD = 22, male = 12 5.6-12. nds as collaborators on research teams could help identify potential areas of research bias as the study methods are in the development stage and in the interpretation of the results. This community-based participatory research approach is gaining momentum in health-based research, with the ultimate goal of improving the science of addressing health disparities in socially disadvantaged population groups [75][76][77][78].…”
Section: Dsm-5 Nomentioning
confidence: 99%
“…Lim, O'Sullivan, Choi and Kim, 2016 [55] n = 30; ASD =15, male = 13 8.4-14 yrs. DSM-IV No Manfredi, Riefoli, Coviello and Dibello, 2022 [56] n = 22; ASD = 22, male = 12 5.6-12. nds as collaborators on research teams could help identify potential areas of research bias as the study methods are in the development stage and in the interpretation of the results. This community-based participatory research approach is gaining momentum in health-based research, with the ultimate goal of improving the science of addressing health disparities in socially disadvantaged population groups [75][76][77][78].…”
Section: Dsm-5 Nomentioning
confidence: 99%
“…8 Researches showed that children with TW and ASD need a longer duration of physical therapy intervention. 9 CP is an umbrella term referring to movement impairments caused by injury to the central nervous system. 10 Children with CP have flat caused of the reduced plantar activity in the second part of the swing phase.…”
Section: Introductionmentioning
confidence: 99%